PENENTUAN UMUR PANEN DAN PENGARUHNYA TERHADAP KUALITAS BUAH SALAK (Salacca zalacca) - Rosmala, Elis; Trisnaningsih, Umi; Budirokhman, Dodi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2025)
Salak (Salacca zalacca) is one of Indonesia’s important tropical fruits with high economic potential, both for domestic consumption and export. However, its short shelf life and rapid deterioration require proper postharvest handling, particularly determining the optimal harvest maturity. Harvest age strongly influences the physical and chemical quality of salak, which directly affects consumer acceptance and marketability. This study aimed to determine the effect of harvest age on the quality attributes of salak Pondoh fruit. The experiment was conducted in Cimara Village, Kuningan District, from April to August 2020, and continued with laboratory analysis until October 2020. The study used a completely randomized design (CRD) with seven harvest ages: 120, 130, 140, 150, 160, 170, and 180 days after pollination (DAP), each replicated four times, with a total of 224 fruits. Observations were carried out on fresh weight, weight loss after storage, fruit firmness, total soluble solids (TSS), and vitamin C content. Data were analyzed using analysis of variance (ANOVA) followed by the Least Significant Range (LSR) test at a 5% level. The results showed that harvest age significantly affected all measured parameters. Fruits harvested at 180 DAP had the highest fresh weight and lowest weight loss, while vitamin C content decreased with increasing maturity. Fruit firmness declined with later harvest, but TSS values increased, indicating higher sweetness. The best overall fruit quality was obtained at 180 DAP, where salak fruit displayed optimal size, sweetness, and acceptable firmness, despite reduced vitamin C levels. In conclusion, harvesting salak at 180 days after pollination provides the best balance of physical and chemical qualities to meet consumer preferences. Keywords: salak, harvest age, fruit quality, firmness, vitamin C, total soluble solids.